High-Speed Railways and Firms Total Factor Productivity: Evidence from a Quasi-Natural Experiment - Anna Bottasso; Maurizio Conti; Antonella Rita Ferrara; Simone Robbiano (Institute of Labor Economics (IZA), 2023)
The focus of this study is to assess the causal impact of the connection of a local area to a high-speed rail network (HSR) on firms' total factor productivity (TFP). The quasi-random location of the HSR station in the Italian city of Reggio Emilia is exploited in a Difference-in Differences (DiD) research design applied to a large sample of firms, observed over the period 2010-2018. The results suggest that the opening of the HSR station improved treated firms' TFP of about 5%; in particular, such effect is larger for firms closer to the HSR station and slightly increases over the sample period. We also find that the impact of the connection to the HSR station is heterogeneous across industries and depends on firms' size and past productivity. Overall results are robust to a large number of sensitivity checks and falsification tests.
Keywords: C50; D24; L92; R30; 330; transport infrastructure; Difference-in-Differences; total factor productivity